When Local Praise Becomes Cheap Talk - Analyzing the Relationship between Reviewer Location and Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis; van Straaten, Dirk (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
With a growing number of online reviews, it becomes increasingly important for customers and online review platforms to find groups of reviewers who write useful reviews. Customers who review local offline businesses such as restaurants can identify themselves as locals or travelers and thus implicitly assign themselves to a specific reviewer group. This study investigates the relationship between identifying as a local and the perceived usefulness of their online reviews. Using data from Yelp.com, we empirically test hypotheses derived from attribution theory. Our results suggest that neutral and negative reviews by locals tend to be perceived as more useful than reviews by travelers. Positive reviews by locals, however, are not perceived as more useful. These findings provide significant practical implications for online review platforms and local offline businesses.

Sorting Out the Lemons - Identifying Product Failures in Online Reviews and their Relationship with Sales - Gutt, Dominik (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
It is well-established that both average online ratings and the number of ratings positively impact product sales. Yet, the economic implications of the information contained in the online review texts is not that well understood. In this study, we contribute to the understanding of online review texts and its economic implications by conducting and validating an unsupervised machine learning algorithm, the latent dirichlet allocation, to identify online reviews that mention product failures. Furthermore, we show that the textual information on product failures are associated with lower product sales. Our results help online review system designers, e.g., amazon, to identify these reviews and to make them easily accessible to potential customers to support the customer’s purchasing decision. Academics can build on our results by applying our validated topic identification strategy and by linking reviews mentioning product failure to a range of different outcomes.

More than skills: A novel matching proposal for multiplayer video games - Stroh-Maraun, Nadja; Kaimann, Daniel; Cox, Joe (Entertainment Computing)

How effective are leniency programs in cartel deterrence - An overview of the empirical and experimental literature - Arfeen, Muhammad Fahad

Die Deutsche Fußball Liga GmbH - ein Syndikat? Die Zentralvermarktung der Live-TV-Übertragungsrechte aus wettbewerbspolitischer Sicht - Kersting, Florian

Das Zusammenschlussvorhaben der REWE Markt GmbH und Coop eG - eine wettbewerbspolitische Analyse - Beichl, Philipp

Decomposing the Variance of Consumer Ratings and the Impact on Price and Demand - Zimmermann , Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barry (Information Systems Research)
Consumer ratings play a decisive role in purchases by online shoppers. Although the effect of the average and the number of consumer ratings on future product pricing and demand have been studied with some conclusive results, the effects of the variance of these ratings are less well understood. We develop a model which considers durable goods that are characterized by three types of attributes: search attributes, experience attributes, and transformed attributes the latter are conventional experience attributes that are transformed by consumer ratings into attributes that can be searched. Using informed search attributes to refer to the combination of search attributes and transformed attributes, we consider two sources of variance of consumer ratings: taste differences about informed search attributes and quality differences in the form of product failure representing experience attributes. We find that (i) optimal price increases and demand decreases in variance caused by informed search attributes, (ii) optimal price and demand decrease in variance caused by experience attributes, and (iii) by holding the average rating as well as the total variance constant, for products with low total variance price and demand increase in the relative share of variance caused by informed search attributes. Counter to intuition, we demonstrate that risk averse consumers may prefer a higher priced product with a higher variance in ratings when deciding between two similar products with the same average rating. Finally, our model provides a theoretical explanation for the empirically observed j-shaped distribution of consumer ratings in e-commerce that differs from established explanations.

Wissensarbeit mit Social Media Plattformen – Unsicherheitsfaktoren als Managementansatz - Trier, Matthias (HMD Praxis der Wirtschaftsinformatik)

Beschreib mir deine Wohnung und ich sag dir wer du bist - Eine explorative Analyse von Gastgeberpersönlichkeiten auf Airbnb - Müller, Michelle; Gutt, Dominik; Neumann, Jürgen (Multikonferenz Wirtschaftsinformatik (MKWI) 2018)

A Duration Model Analysis of Consumer Preferences and Determinants of Video Game Consumption - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Journal of Consumer Behaviour)

Heuristics and Simulation for Water Tank Optimization - Hallmann, Corinna; Burmeister, Sascha Christian; Wissing, Michaela; Suhl, Leena (Communications in Computer and Information Science)

Model Generator for Water Distribution Systems - Hallmann, Corinna; Kuhlemann, Stefan (Operations Research Proceedings)

Innovationsförderung durch Transferagenturen - Erfahrungen im Aufbau von Transferagenturen zur Förderung eines datenbasierten kommunalen Bildungsmanagements

A Note on Manipulability in School Choice with Reciprocal Preferences - Haake, Claus-Jochen; Stroh-Maraun, Nadja
We show that the Boston school choice mechanism (BM), the student proposing deferred acceptance algorithm (DA) and the top trading cycles algorithm (TTC) generate the same outcome when the colleges’ priorities are modified according to students’ preferences in a “first preferences first” manner. This outcome coincides with the BM outcome under original priorities. As a result, the DA and TTC mechanism that are non-manipulable under original priorities become vulnerable to strategic behavior.

Does Informational Equivalence Preserve Strategic Behavior? An Experimental Study on Trockel's Game - Duman, Papatya
The purpose of the present study is to experimentally test a version of the classical Chain Store Game (CSG) paradox, proposed by Trockel (1986), and determine whether one of the two theories of Induction and Deterrence, which were originally tested competitively by Selten (1978), may better account for the results. With complete and perfect information, the CSG of Selten (1978) was designed to analyze the role of reputation in repeated market interactions. Its results were discussed in two diﬀerent ways: one is based on backward induction, and the other is intuitively derived from a deterrence argument. As the two explanations are incompatible, alternative models have been proposed to understand them better. The alternative game proposed by Trockel is an imperfect information version of the CSG in which the order of the two players is changed in each round and the ’Out-Aggressive’ equilibrium is used to build reputation. The existence of more than one equilibrium is the basis for the building of reputation. To the best of my knowledge, this study is the ﬁrst attempt to experimentally test this alternative game with the same purpose.
Keywords: Chain Store Game; reputation building; entry deterrence; Trockel's game

Participatory Budgeting: Findings From Germany - Weber, Henriette I.; Vogt, Sebastian; Eberz-Weber, Lisa-Marie; Steinmetz, Holger; Wagner, Sascha A.; Walther, Falko; Weber, Patrick; Kabst, Rüdiger (Civic Engagement and Politics: Concepts, Methodologies, Tools, and Applications)
Consultative participation of citizens in political decision-making processes has been increasing in order to facilitate democratic legitimacy and responsiveness. Consequently, participatory budgets have been established as a 'best practice' for consultative participation of citizens in political decision-making processes. The authors compare participatory budgets of 31 German municipalities. An analysis of differences between successfully and unsuccessfully rated participatory budgeting processes provides informative insights and allows for in-depth comparison on a municipal level. The authors show that external service providers and electronic participation channels significantly increase the number of participatory citizens and are positively connected with pursued objectives of dialog processes and public responsiveness as well as efficient and effective decisions. Furthermore, the acceptance of all participants proved to be a key factor for a successful public participation process. The authors' analysis opens up new starting points for further research.

Kommentar: MaGo – Aufsichtsrechtliche Mindestanforderungen an die Geschäftsorganisation von Versicherungsunternehmen - Krimphove, Dieter; Kruse, Oliver

Financial penalties and banks’ systemic risk - Köster, Hannes; Pelster, Matthias (The Journal of Risk Finance)

Bank stock performance and bank regulation around the globe - Pelster, Matthias; Irresberger, Felix; Weiß, Gregor N.F. (The European Journal of Finance)

Affect and stock returns - Breitmayer, Bastian; Pelster, Matthias (Journal of Behavioral and Experimental Finance)